2020
DOI: 10.1093/ajcp/aqaa160
|View full text |Cite
|
Sign up to set email alerts
|

Nested Variant of Urothelial Carcinoma Is a Luminal Bladder Tumor With Distinct Coexpression of the Basal Marker Cytokeratin 5/6

Abstract: Objectives The nested variant of urothelial carcinoma (NVUC) is a rare bladder tumor that may possess a luminal molecular phenotype. We sought to determine whether a small immunohistochemical (IHC) panel using common surrogates for molecular phenotypes would reliably classify a cohort of pure NVUC cases. Methods IHC staining with a panel composed of markers for basal subtypes (CK5/6, CK14) and luminal subtypes (FOXA1, GATA3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Divergent Differentiation/Histological Subtype IHC-Based Molecular Cluster [13,22,25,26,48,101] Squamous Mostly basal [22,25,27,35,102] Glandular Variable [13,32,67,101,[103][104][105] Micropapillary Mostly luminal (LumNS) [13,68,[106][107][108][109] Nested and large nested Mostly luminal (LumP) [27,29,69,101,107,110] Plasmacytoid Mostly luminal [23,26,29,32,34] Sarcomatoid Variable…”
Section: Reference [N#]mentioning
confidence: 99%
See 1 more Smart Citation
“…Divergent Differentiation/Histological Subtype IHC-Based Molecular Cluster [13,22,25,26,48,101] Squamous Mostly basal [22,25,27,35,102] Glandular Variable [13,32,67,101,[103][104][105] Micropapillary Mostly luminal (LumNS) [13,68,[106][107][108][109] Nested and large nested Mostly luminal (LumP) [27,29,69,101,107,110] Plasmacytoid Mostly luminal [23,26,29,32,34] Sarcomatoid Variable…”
Section: Reference [N#]mentioning
confidence: 99%
“…Recently, Johnson et al reported on the co-expression of luminal (FOXA1, GATA3) and basal (CK5/6) markers in a cohort of NCs, the latter displaying marked heterogeneity in a subset of cases [109], in keeping with the results from the study by Warrick et al [102], consisting with the Uro subtype according to the Lund classification [23,101]. Tumors belonging to this subtype share with NCs some histological features, such as a smooth tumor-stroma interface and nuclear monomorphism, as seen in pure NCs [22].…”
Section: Nested and Large Nested Carcinomamentioning
confidence: 99%
“…The low Ki67 proliferation rate in nested carcinoma renders this immunostain less useful 12,14. TERT promoter mutations occur in the majority of nested UC cases but not benign mimickers 16–19. Nested UCs express PAX8, which may represent a diagnostic pitfall vis a vis nephrogenic adenoma in cases with microcystic components20,21 Nested UCs appear to express luminal markers more frequently than basal markers and harbor an exceptionally low frequency of FGFR3 mutations (<5%), likely limiting the usefulness of treatments that target FGFR3 -mutated cancers 13,19.…”
Section: Histologic Subtype/variant Morphology In Urothelial Carcinomamentioning
confidence: 99%
“…12,14 TERT promoter mutations occur in the majority of nested UC cases but not benign mimickers. [16][17][18][19] Nested UCs express PAX8, which may represent a diagnostic pitfall vis a vis nephrogenic adenoma in cases with microcystic components 20,21 Nested UCs appear to express luminal markers more frequently than basal markers and harbor an exceptionally low frequency of FGFR3 mutations (< 5%), likely limiting the usefulness of treatments that target FGFR3-mutated cancers. 13,19 From a practical viewpoint, the correct diagnosis in most settings requires careful histologic examination; the value of ancillary studies is fairly limited.…”
Section: Histologic Subtype/variant Morphology In Urothelial Carcinomamentioning
confidence: 99%
“…19,37 Micropapillary, plasmacytoid, nested, and large nested subtypes typically have a luminal expression subtype. 33,[38][39][40][41][42][43] Invasive carcinoma with divergent differentiation may differ in molecular subtype from invasive urothelial carcinoma NOS, or other histomorphologies, present in spatially distinct parts of the same tumor. 21,33,36,38,[44][45][46][47] This is best studied in urothelial carcinoma with squamous differentiation.…”
Section: Bladder Cancer May Change Molecular Subtype As the Tumor Evo...mentioning
confidence: 99%